2008
DOI: 10.1016/j.janxdis.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and disinhibition: An analysis of curiosity and social rank appraisals, approach–avoidance conflicts, and disruptive risk-taking behavior

Abstract: We examined how social anxiety is related to appraisals for various disinhibited behaviors and sought to identify potential subgroups of socially anxious people. College students completed trait measures and appraised disinhibited behaviors on their potential for threat, opportunity to satisfy curiosity, and ability to enhance social status. Three months later, participants were asked to report on their frequency of disinhibited behaviors since the initial assessment. People with greater social anxiety demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 45 publications
(70 reference statements)
7
89
0
Order By: Relevance
“…Previous research has identified subgroups of anxiousimpulsive and anxious-inhibited young adults, and com- pared them regarding external adjustment [1][2][3]. Going beyond previous research, however, we attempted to identify these subgroups in a general population, compare them on levels of internal adjustment, as well as examine if these associations were moderated by gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has identified subgroups of anxiousimpulsive and anxious-inhibited young adults, and com- pared them regarding external adjustment [1][2][3]. Going beyond previous research, however, we attempted to identify these subgroups in a general population, compare them on levels of internal adjustment, as well as examine if these associations were moderated by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of socially anxious people fit this description, an unexpected or atypical subgroup has recently been identified. Rather than being inhibited, this subgroup of socially anxious people appear to be impulsive [1][2][3]. What could be the reasons for this atypical pattern of characteristics, and what does it imply for the life experiences and adaptation of socially anxious individuals?…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additional evidence was found in two studies that examined differences in appraisal patterns and novelty-seeking tendencies for risky social situations (Kashdan, Elhai, & Breen, 2008;Kashdan & Hofmann, 2008). These studies used cluster-analytic techniques to identify subgroups of individuals with social anxiety characterized by distinct patterns of approach/avoidance appraisals for social activities and risk-taking behaviors.…”
Section: Social Anxiety and Angermentioning
confidence: 95%
“…Indeed, there is some naturalistic evidence for such a 179 mechanism. Some individuals with high levels of social anxiety demonstrate high levels of risk--taking 180 behaviour on questionnaire measures (Kashdan et al, 2006, Kashdan et al, 2008, Kashdan and 181 McKnight, 2010. This may, in turn, explain some of the discrepancies across prior studies.…”
Section: Reaction Times 138mentioning
confidence: 99%